Pengaruh Kemampuan dan Kepuasan Kerja Terhadap Kinerja Pegawai Kelurahan Puruk Cahu Kecamatan Murung Kabupaten Murung Raya - Kadir, Abdul; Efrianti, Kumara (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2018)
This study aims to determine whether there is influence of ability and job satisfaction on employee performance in Puruk Cahu Village, Murung Subdistrict, Murung Raya District, either partially or simultaneously. The method used in this study is quantitative research, which is a research model that requires the calculation of numbers, while the approach used is a survey approach, namely research that takes samples from the population and uses questionnaires as the main data collection tool. The results of this study indicate that the variables of ability and job satisfaction have a significant effect and the changes change in line with the performance of the employees of the Puruk Cahu Village, Murung Village, Murung Raya District. This means that if the level of influence of ability and job satisfaction is felt to be higher, then the higher the performance will also result.